2018
DOI: 10.1017/jfm.2018.234
|View full text |Cite
|
Sign up to set email alerts
|

Onset of transition in the flow of polymer solutions through microtubes

Abstract: Experiments are performed to characterize the onset of laminar–turbulent transition in the flow of high-molecular-weight polymer solutions in rigid microtubes of diameters in the range $390~\unicode[STIX]{x03BC}\text{m}{-}470~\unicode[STIX]{x03BC}\text{m}$ using the micro-PIV technique. By considering flow in tubes of such small diameters, the present study probes higher values of elasticity numbers ($E\equiv \unicode[STIX]{x1D706}\unicode[STIX]{x1D708}/R^{2}$) compared to existing studies, where $\unicode[STI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(93 citation statements)
references
References 46 publications
29
64
0
Order By: Relevance
“…In the inset, ¢( ) G f and ( ) G f have been plotted against frequency which has been calculated theoretically using the extracted parameter values of the fluid. [33]. The trends of the variation of λ with concentration for our values and those reported earlier clearly appear to be similar.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In the inset, ¢( ) G f and ( ) G f have been plotted against frequency which has been calculated theoretically using the extracted parameter values of the fluid. [33]. The trends of the variation of λ with concentration for our values and those reported earlier clearly appear to be similar.…”
Section: Resultssupporting
confidence: 89%
“…We test our technique on a purely viscous fluid-water, for which we obtain very good agreement with well-known literature values, and different viscoelastic solutions of PAM and water where the concentration of the former is varied. At low polymer concentrations, we obtain rather reliable measurements of the time constant λ which match with values in literature [33], while for increased polymer concentrations, the values seem to be unreliable with very small change in the measured μ p with increasing concentration. This we attribute to the limitations of our theory in the case of non-linear viscoelastic fluids and for more complex fluids with additional time constants, which probably is the case when we increase the concentration of PAM in the solution.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The lack of a hysteretic signature in the experiments of Samanta et al (2013) served as a primary motivation in our search (Garg et al 2018) for a linear instability in viscoelastic pipe flow. The recent experimental work of Chandra et al (2018Chandra et al ( , 2020 further corroborated the findings of Samanta et al (2013), and reported a decrease in the transition Re with increasing concentration in the range 300-800 ppm.…”
Section: Early Transition and Eitsupporting
confidence: 64%
“…While channel flow exhibits a two-dimensional linear instability leading to so-called Tollmien-Schlichting (TS) waves, the critical Reynolds number Re = 5772 is much higher than that observed for transition, so these are not traditionally viewed as playing an important role in Newtonian transition.For flowing polymer solutions under some conditions (low concentration, short polymer relaxation times), transition to turbulence occurs via the usual bypass transition. With further increase in Re, drag reduction sets in, and the flow eventually approaches the so-called maximum drag reduction (MDR) asymptote, an upper bound on the degree of drag reduction that is insensitive to the details of the fluid.Under other conditions, flow transitions directly from laminar flow into the MDR regime, and can do so at a Reynolds number where the flow would remain laminar if Newtonian [2][3][4][5]. Recent experiments and simulations [6][7][8] suggest that turbulence in this regime has structure very different from Newtonian, denoting it as "elastoinertial turbulence" (EIT).…”
mentioning
confidence: 99%